2018
DOI: 10.1007/s10826-018-1242-x
|View full text |Cite
|
Sign up to set email alerts
|

Parenting Styles: A Closer Look at a Well-Known Concept

Abstract: Although parenting styles constitute a well-known concept in parenting research, two issues have largely been overlooked in existing studies. In particular, the psychological control dimension has rarely been explicitly modelled and there is limited insight into joint parenting styles that simultaneously characterize maternal and paternal practices and their impact on child development. Using data from a sample of 600 Flemish families raising an 8-to-10 year old child, we identified naturally occurring joint p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
138
1
26

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(216 citation statements)
references
References 83 publications
(171 reference statements)
3
138
1
26
Order By: Relevance
“…Most parents participating in this research had congruent parenting styles in terms of authoritative parenting. In line with results of this study, it is showed parents who had high levels of agreement in parenting styles were those who adopted positive parenting, whereas those exhibiting low agreement in parenting approaches were couples who implemented ineffective parenting (Kuppens & Ceulemans, 2019).…”
Section: Discussionsupporting
confidence: 87%
“…Most parents participating in this research had congruent parenting styles in terms of authoritative parenting. In line with results of this study, it is showed parents who had high levels of agreement in parenting styles were those who adopted positive parenting, whereas those exhibiting low agreement in parenting approaches were couples who implemented ineffective parenting (Kuppens & Ceulemans, 2019).…”
Section: Discussionsupporting
confidence: 87%
“…In this typology, parenting styles are defined as authoritarian (high control but low involvement) authoritative (high control and high involvement), indulgent or permissive (low control but high involvement) and neglectful (low control and low involvement). These parenting styles have been supported both conceptually and empirically in relation to developmental outcomes for children (see Kuppens and Ceulemans, 2019, for a recent review). General parenting style then, may dictate the type of approach parents take to managing cyber security in the family.…”
Section: Introductionmentioning
confidence: 99%
“…However, existing literature mostly focused on parental monitoring as a mediating variable rather than exploring its direct effects on problem behaviors (e. g., alcohol use; Kim & Neff, 2010), For instance, Barnes, Reifman, Farrell, and Dintcheff (2000) in their six-waves longitudinal analyses provided evidence that monitoring mediated the linkage between parental support and alcohol misuse. In the attempt to fill this gap, the current study investigated such a specific dimension of parenting, i. e. parental monitoring (Kuppens & Ceulemans, 2019) in order to enhance the knowledge about the beneficial impact of parents' active supervision on adolescents' positive outcomes, in terms of healthy use of either food or alcohol. As to this, it is reasonable to suppose that parents who do not adequately monitor their offspring are less involved in their lives and, consequently, may neglect the first signs of problematic behaviors (i.e., binge drinking or eating) of youngsters.…”
Section: Satisfactionmentioning
confidence: 99%